ANALISIS DAMPAK COVID-19 TERHADAP KINERJA KEUANGAN PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pratama, Enriko Haris; Pontoh, Winston; Pinatik, Sherly (Universitas Sam Ratulangi, 2021)
Thissexplorationnobject is toonoticing Â theeeffect offCOVID-19 on the monetary execution of retail organizations recorded on the IDX (Indonesian Stock Exchange), by looking at monetary information prior and then afterward COVID-19, utilizing monetary proportions of productivity which are ROA, ROE, and NPM of recorded retail organizations. quantitative descriptive technique are utilized in this exploration, then, at that point information will be handled utilizing a combined example t-test utilizing the SPSS 25 program. The aftereffects of this examination demonstrate that: (1) Thereeare huge contrasts in the Returnnon Assets of retail organizations recorded on the Indonesia Stock Exchange prior and then afterward COVID-19. This is displayed from the aftereffects of the critical worth which is more modest thann0.05; (2) There is a huge contrast in the Returnnon Equity of retail organizations recorded on the Indonesia Stock Exchange prior and then afterward COVID-19. This is demonstrated by the importance esteem which is more modest thann0.05; (3) There is no critical contrast in the NettProfit Margin of retail organizations recorded in Indonesia Stock Exchange prior and then afterward COVID-19. This is demonstrated by importance esteem bigger thann0.05.